2000
DOI: 10.1093/intimm/12.1.73
|View full text |Cite
|
Sign up to set email alerts
|

CD137 (ILA/4-1BB), expressed by primary human monocytes, induces monocyte activation and apoptosis of B lymphocytes

Abstract: Human CD137 is a member of the tumor necrosis factor (TNF) receptor family and the homologue of murine 4-1BB. Recent studies have demonstrated that CD137 promotes accessory T cell activation, and regulates proliferation and survival of T lymphocytes. This study reports on the expression and function of CD137 in peripheral blood monocytes. While monocytes showed constitutive expression in 10 out of 18 healthy donors, CD137 was not expressed on resting T or B lymphocytes. Immobilized antibodies to CD137 markedly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 48 publications
3
64
0
1
Order By: Relevance
“…Reverse signaling following cross-linking of 4-1BBL in lymphocytes inhibits proliferation and induces apoptosis Ebta et al, 2001). In addition, 4-1BB also causes apoptosis of B-cells by direct cell contact (Kienzle and Kempis, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Reverse signaling following cross-linking of 4-1BBL in lymphocytes inhibits proliferation and induces apoptosis Ebta et al, 2001). In addition, 4-1BB also causes apoptosis of B-cells by direct cell contact (Kienzle and Kempis, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA (2 lg) was reverse-transcribed with (dT) 16 and 1 lL of Superscript II enzyme (Invitrogen, Carlsbad, CA) in 20 lL reaction mix at 42 C for 1 h. For real-time PCR, a 20-lL reaction mix containing 1 lL template cDNA, SYBR Premix Ex Taq, ROX Reference Dye (Takara Bio, Otsu, Japan), and each primer (0.2 lM) was prepared and subjected to amplification using a fluorescence thermocycler (Applied Biosystems 7500 Real-time PCR, Foster City, CA) under the following conditions: initial denaturation at 94 C for 1 min, followed by 40 cycles of denaturation at 95 C for 15 s, annealing at 60 C for 15 s, and elongation at 72 C for 33 s. The specificity of the PCR product was verified by melting curve analysis and examination on a 3% agarose gel. The housekeeping GAPDH gene was amplified in parallel with the gene of interest.…”
Section: Real-time Sqrt-pcrmentioning
confidence: 99%
“…In addition, the intracellular signaling pathways downstream of 4-1BB and RANK are very similar [13,14]. Recent studies showed that 4-1BB is expressed on dendritic cells and monocytes as well as on T cells, and modulates the function of these cells [15,16]. Furthermore, reverse signaling through 4-1BBL on monocytes induces the secretion of inflammatory cytokines, monocyte proliferation, and endomitosis [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…18 In addition to CD4 þ and CD8 þ T cells, 4-1BB was also expressed on activated natural killer (NK), 22 dendritic cells (DC) 23 as well as neutrophils 24 in mice. In humans, the expression of 4-1BB was been reported in follicular DCs, 25 monocytes, 26 hepatoma cells 18 and blood vessels from individuals with malignant tumors. 27 The soluble form of 4-1BB was also reported in the serum of patients with rheumatoid arthritis.…”
Section: Expression Of 4-1bb and 4-1bbl In Vivomentioning
confidence: 97%